2007
DOI: 10.1186/1471-2288-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of locating women six to eight years after contact: internet resources at recruitment may help to improve response rates in longitudinal research

Abstract: Background: The ability to locate those sampled has important implications for response rates and thus the success of survey research. The purpose of this study was to examine predictors of locating women requiring tracing using publicly available methods (primarily Internet searches), and to determine the additional benefit of vital statistics linkages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Unsurprisingly, the strongest predictor of completing a given follow-up interview was having completed the previous one, consistent with other studies that have emphasized the importance of maintaining participant contact (Cadarette et al, 2007;Gilmore & Kuperminc, 2014;Hobden et al, 2011;Scott, 2004;Scott et al, 2006). Notably, with the exception of other opiate use and treatment status, all other time-varying participant characteristics were nonsignificant, but the fixed covariates of incarceration and years of schooling remained.…”
Section: Discussionsupporting
confidence: 84%
“…Unsurprisingly, the strongest predictor of completing a given follow-up interview was having completed the previous one, consistent with other studies that have emphasized the importance of maintaining participant contact (Cadarette et al, 2007;Gilmore & Kuperminc, 2014;Hobden et al, 2011;Scott, 2004;Scott et al, 2006). Notably, with the exception of other opiate use and treatment status, all other time-varying participant characteristics were nonsignificant, but the fixed covariates of incarceration and years of schooling remained.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, 29% of the sample was located using this strategy. In comparison, an earlier study documents locating 50% of women sampled after six to 8 years without contact using web-searches [5]. The study suggested that researchers interested in longitudinal designs include the listed name for telephone numbers of participants identified through web-resources as part of their study design.…”
Section: Discussionmentioning
confidence: 98%
“…In the absence of updated information, the feasibility of tracing participants for longitudinal research is questionable. This may be particularly true when tracing female participants [4,5] and when tracing participants that reside in areas that exhibit high residential mobility. For instance, earlier research traced fewer than one-third of women to their known addresses by solely relying on name searches on the Internet [4].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These reports also provide recommendations for appropriate statistical strategies and techniques for analyses in the presence of missing data. Some strategies for locating patients who fail to return for followup include using the Internet and other public data sources such as motor vehicle registration records and credit bureau databases [5,14,18,29]. These methods have varying success and often require crossreferencing multiple such resources.…”
Section: How Do We Get There?mentioning
confidence: 99%